2022
DOI: 10.2196/39144
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Motivations for COVID-19 Vaccination Among Black Young Adults in 3 Southern US States: Cross-sectional Study

Abstract: Background Few studies have focused on attitudes toward COVID-19 vaccination among Black or African American young adults (BYA) in the Southern United States, despite high levels of infection in this population. Objective To understand this gap, we conducted an online survey to explore beliefs and experiences related to COVID-19 vaccination among BYA (aged 18-29 years) in 3 southern states. Methods We recrui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 32 publications
2
11
1
Order By: Relevance
“…Overall, a large majority of our patients—79%—perceived that COVID-19 was risky and dangerous, and 65% considered the vaccines to be safe, similar to prior results in cancer patient studies [ 25 , 28 , 29 , 30 , 33 , 35 , 41 , 42 , 43 , 44 ]. Other self-reported reasons for being vaccinated stated by our participants included protecting themselves, family, and friends, the collective good of ending the pandemic, and trust in the vaccine and science; again, these were very similar to previous studies in cancer patients and ethnic minorities [ 23 , 25 , 28 , 29 , 31 , 35 , 50 ]. Participants who had self-reported a fair or excellent health at the time of the survey were seen to have a significantly higher likelihood of being vaccinated, 22 times more likely compared with those who self-reported poor health, according to our multivariable logistic regression and multinomial logistic regression models ( Table 2 and Table 3 ); this represents another factor to consider when examining future vaccine uptake studies in this population.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…Overall, a large majority of our patients—79%—perceived that COVID-19 was risky and dangerous, and 65% considered the vaccines to be safe, similar to prior results in cancer patient studies [ 25 , 28 , 29 , 30 , 33 , 35 , 41 , 42 , 43 , 44 ]. Other self-reported reasons for being vaccinated stated by our participants included protecting themselves, family, and friends, the collective good of ending the pandemic, and trust in the vaccine and science; again, these were very similar to previous studies in cancer patients and ethnic minorities [ 23 , 25 , 28 , 29 , 31 , 35 , 50 ]. Participants who had self-reported a fair or excellent health at the time of the survey were seen to have a significantly higher likelihood of being vaccinated, 22 times more likely compared with those who self-reported poor health, according to our multivariable logistic regression and multinomial logistic regression models ( Table 2 and Table 3 ); this represents another factor to consider when examining future vaccine uptake studies in this population.…”
Section: Discussionsupporting
confidence: 84%
“…This concern is further amplified if a patient with COVID-19 is not only unvaccinated but also has comorbidities such as cancer, predisposing them to higher risk of morbidity and mortality. COVID-19 vaccine hesitancy has been studied previously in cancer patients worldwide [ 25 , 26 , 27 , 28 , 29 , 30 , 32 , 39 , 40 , 41 , 42 , 43 , 44 ] and in the United States [ 31 , 33 , 35 , 36 , 45 ], including multiple studies of ethnic minorities in the US [ 21 , 22 , 23 , 24 , 46 , 47 , 48 , 49 , 50 , 51 ], but no known research exists specifically examining ethnic minority cancer patients and their views on the COVID-19 vaccine. This study helps address this gap in the knowledge by uniquely examining two different time-points of vaccination status 6-months post-initial survey, employing a vaccine knowledge score composite and exploring a brief educational intervention to raise patients’ awareness, to gain valuable insight into this distinctly disadvantaged population in the US.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Digital storytelling workshop participants were recruited through an online survey fielded in the larger study (N=150) from August 2021 to November 2021 and described elsewhere [ 21 ]. Respondents all self-identified as Black in survey demographic questions in the larger study from which workshop participants were identified.…”
Section: Methodsmentioning
confidence: 99%